Three-dimensional pharyngeal airway space changes after bimaxillary advancement - Thaís Lima ROCHA; Ludmila LIMA; Arnaldo PINZAN; Eduardo SANT'ANA; Renato Luiz Maia NOGUEIRA; Caroline Nemetz BRONFMAN; Guilherme JANSON (Dental Press Editora, 2021)
ABSTRACT Introduction: The probability of improvement in the upper airway space (UAS) with orthognathic surgery should be considered during the surgical-orthodontic treatment decision, providing not only an esthetic, but also a functional benefit for the patient. Objective: The purpose of this study was to evaluate the 3D changes in the upper airway space after maxillomandibular advancement surgery (MMA). Methods: A retrospective analysis of 56 patients, 21 male and 35 female, with a mean age of 35.8 ± 10.7 years, who underwent MMA was performed. Pre- and postoperative cone-beam computed tomography scans (CBCT) were obtained for each patient, and the changes in the UAS were compared using Dolphin Imaging 11.7 software. Two parameters of the pharyngeal airway space (PAS) were measured: airway volume (AV) and minimum axial area (MAA). Paired t-test was used to compare the data between T0 and T1, at 5% significance level. Results: There was a statistically significant increase in the UAS. Bimaxillary advancement surgery increased the AV and the MAA, on average, by 73.6 ± 74.75% and 113.5 ± 123.87%, respectively. Conclusion: MMA surgery tends to cause significant increase in the UAS; however, this increase is largely variable.